A Replication of "The Macroeconomic Impact of Europe's Carbon Taxes" by Metcalf and Stock (2023) - Thomas Ash; Giorgi Nikolaishvili (Institute for Replication (I4R), 2024)
Metcalf and Stock (2023) find that an increase in carbon tax has a weakly positive effect on output and employment, along with a negative effect on C02 emissions over a 6-year horizon. The paper identifies a carbon tax shock and uses it to quantify the effect of a permanent unexpected increase in the carbon tax rate. The effect of this increase is obtained using a policy counterfactual exercise based on dynamic effects estimated using panel local projections. We use the authors' own Stata replication package to reproduce the main results of the paper and carry out additional robustness tests. We also conduct these empirical analyses using popular open-source econometric libraries in R. We compare the original permanent carbon tax increase policy counterfactual impulse responses to standard one-time carbon tax shock impulse responses. The justification for this robustness test is that carbon tax rate changes are persistent, so that a transitory shock effectively mimics a permanent shock. We find that (1) the authors' replication package successfully reproduces the results of the paper; (2) alternative local projection specifications and policy counterfactuals largely exhibit the same qualitative properties as the main results of the paper.
Keywords: E23; E24; H23; Q54; Q58; 330; carbon tax; policy counterfactual; panel local projection